Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan yang Dimoderasi Ukuran Perusahaan - Meliza Meliza; Sifa Urrohman; Aria Mulyapradana (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
This study aims to explore the influence of capital structure and profitability on firm value, considering firm size as a moderating variable. Capital structure and profitability are considered important components in assessing financial performance and investment attractiveness. Firm size is assumed to have the potential to strengthen or weaken the relationship between these two main variables on firm value. This study used a sample of 25 companies from the consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The analysis was conducted using a multiple regression method using a fixed-effects (FE) approach to test the direct influence and moderating role of firm size. The results show that capital structure and profitability have a positive and significant influence on firm value. However, firm size was not proven to moderate the relationship between capital structure and profitability on firm value